Chlamydomonas as a tool to study tubulin polyglutamylation. (26th October 2018) - Kubo, Tomohiro; Oda, Toshiyuki
Abstract : α- and β-tubulin undergoes polyglutamylation, a post-translational modification. This modification is important for stability and electrostatic properties of microtubules, thereby affecting functions of various microtubule-associated proteins. Here we review and introduce polyglutamylation of ciliary/flagellar tubulin, mainly focusing on our research using the unicellular green alga Chlamydomonas reinhardtii. Abstract: The diversity of α- and β-tubulin is facilitated by various post-translational modifications (PTMs), such as acetylation, tyrosination, glycylation, glutamylation, phosphorylation and methylation. These PTMs affect the stability and structure of microtubules as well as the interaction between microtubules and microtubule-associated proteins, including molecular motors. Therefore, it is extremely important to investigate the roles of tubulin PTMs for understanding the cell cycle, cell motility and intracellular trafficking. Tubulin PTMs were first studied in the 1980s, and considerable progress has been made since then; it is likely that additional mechanisms remain yet to be elucidated. Here, we discuss one such modification, tubulin glutamylation, and introduce our research on the eukaryotic flagellum of the unicellular green alga Chlamydomonas reinhardtii .